Making the case for self-organisation: understanding how communities make sense of sustainability and climate change through collective action. (2017) - Atkinson, Rob; Dörfler, Thomas; Hasanov, Mustafa; Rothfuß, Eberhard; Smith, Ian
Understanding how community groups take on the challenge of climate change is key to understanding the capacity of society as a whole to adapt in the face of climate change in ways that acknowledge a broader need for a sustainable societal transition. In order to show this it is important to identify what distinguishes self-organised responses to the climate change challenge from other responses. Through critically evaluating the existing literature on self-organisation and on locally based responses to climate change, the paper clarifies what we mean by self-organised response and then demonstrates how the concept would enhance the scope of research about local-level responses to enhance societal sustainability. Furthermore, the article presents an agenda for identifying self-organised responses to climate change and distinguishing self-organised responses from other forms of 'community-led' response.